Road Traffic Injuries in Iran: Epidemiology and Equitable Distribution of Emergency Services - Pirhossein Kolivand; Peyman Saberian; Samad Azari; Peyman Namdar; Fereshte Karimi; Arash Parvari; Seyed Jafar Ehsanzadeh; Behzad Raei; Mehdi Raadabadi; Soheila Rajaie (Bulletin of Emergency and Trauma)
Objective: This study emphasized the importance of providing equal access to rescue and emergency services for all individuals involved in road accidents, regardless of their geographical location or socioeconomic status.Methods: This study involved gathering data on the number of Iranian Red Crescent Society (IRCS) and Emergency Medical Services (EMS) stations in 31 provinces of Iran. It entailed calculating the Gini coefficient and creating the Lorenz curve to assess the station distribution. To present road traffic injuries (RTIs) mortality, Disability-Adjusted Life Years (DALYs), and prevalence in Iran from 1990 to 2019, the Global Burden of Disease (GBD) 2019 estimates were utilized.Results: The findings revealed that Tehran, Khorasan Razavi, Isfahan, Fars, and Khuzestan provinces were equipped with the most stations; whereas, Ilam, Semnan, and Kohgiluyeh and Boyer Ahmad had the fewest. The Gini coefficient for the distribution of RCS and EMS stations was found to be 0.23 and 0.38, respectively. Additionally, the study examined the prevalence, DALYs, and mortalities caused by road injuries across the 31 provinces and presented the findings in the form of a geographical representation.Conclusion: The results of this study highlighted the importance of ongoing efforts to ensure the equitable allocation of RCS and emergency services, with a particular emphasis on road accidents and disaster management scenarios.